Developing digital human resources in the European Union and implications for Vietnam - Trinh Thanh Vinh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
The article analyzes the development of digital human resources in the European Union (EU) and suggests solutions for Vietnam. In the context of global digital transformation, the EU has developed many policies and strategies to improve digital skills for the workforce, from basic to advanced skills. The article also points out the major challenges that the EU faces, including the gap in digital skills, difficulties in retraining workers, and gender inequality in the technology sector. Based on the lessons of the EU, the author offers some suggestions for Vietnam on building a digital skills development strategy, promoting public-private partnerships, and narrowing the skills gap between regions. Code: 24101501